The political value of time citizenship, duration and democratic justice - Cohen, Elizabeth F. 1973- (Cambridge University Press, 2018)
"Time is widely recognized as one of the most precious and finite resources required for the accomplishment of human purposes. Within the domain of the political, time is required for almost any exercise of liberty that people seek to protect through the enforcement of social contracts, constitutions, and laws. Time is therefore inextricable from the realization of any vision of political justice. All political subjects encounter myriad ways in which their time is structured, valued, appropriated, or freed by the state. In the United States, we wait to turn 18 to acquire political voice and full representation. Then we wait again, to turn 62 or 66, when we can retire from work and receive retirement benefits, if we wish. People file taxes on April 15; redistricting hinges on decennial censuses; and prosecutors specify when crimes were committed to determine whether statutes of limitation have expired. Around us convicted criminals are punished with prison sentences of varying durations, legal permanent residents refrain from traveling for long periods of time as they seek to naturalize, and election cycles run their course only to begin anew. Despite the significance of time for the satisfaction of people's ends, the legitimate power of the state to command the time of its subjects and set a political schedule is not generally contested"--Provided by publisher.